ECONOMIC PROBLEMS AS A COMPONENT OF A. LOTOTSKY'S JOURNALISTIC ESSAYS (Південний архів (історичні науки), 2021)
The goal of the work. The article is devoted to covering economic topics as a significant part of O. Lototsky's journalistic research, which complements the intellectual biography of the figure. The historiography of the issue is represented by works devoted specifically to the development of an intellectual biography of Ukrainian figures. This article analyzes the materials of O. Lototsky, which were published in periodicals in the late XIX – early XX centuries. they characterize the issues of peasant and noble land use, problems of lending in the Russian Empire, and so on. Special attention is paid to Lototsky's historical research "the history of state control", dedicated to the 100th anniversary of State control in the Russian Empire.This theme originated in the creative heritage of O. Lototsky as a result of a new field of professional activity. In 1897, he served in the Kiev control chamber, and in 1900 he was transferred from Kiev to the state chamber in St. Petersburg.Scientific novelty and research results. O. Lototsky is better known as a church historian, an active supporter of the idea of proclaiming the autocephaly of the Ukrainian Orthodox Church, a participant in political events in Ukraine during 1917-1920. In recent years, attention has been paid to XIX – to the early 20's of the twentieth century. However, they are somewhat deprived of the attention of modern researchers of O. Lototsky's intelligence on economic issues. Therefore, the scientific novelty consists in highlighting the facts of the creative biography of the scientist, which received only a cursory mention in the works of modern historians, and determining its significance for the reproduction of the intellectual biography of O. Lototsky. Of course, economic topics are not leading in the creative heritage of a scientist. However, given the thorough economic self-education conducted by the scientist, we can emphasize the importance of this aspect of OlexanderIgnatievich's activity. The study of economic topics had a significant impact on the formation of the worldview of th e figure, his political positions.
Keywords: O. Lototsky, intellectual biography, journalistic essays, state control, land ownership, lending.